Efikasi Diri dan Stres Akademik Pada Siswa Sekolah Menengah Atas Program Akselerasi - Silvia Wulandari; Mira Aliza Rachmawati (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2014)
This study aims to determine the relationship between self-efficacy and academic stress on senior high school students who join the acceleration program The hypothesis was that there is a relationship between self-efficacy and academic stress on senior high school students who join the acceleration program. Subjects in this study were 89 senior high school students who join the accelerated program in Yogyakarta. This study uses two scales, namely: (a) the scale of academic stress and (b) self-efficacy scale. Results showed that there is a negative relationship between self-efficacy and academic stress on senior high school students who following an acceleration program. High self-efficacy correlated with low academic stress. Analysis of the coefficient of determination (r2) indicates the contribution of self efficacy of59% against the academic stress students.Keywods: Academic Stress. Self Efficacy, Acceleration Program